2011
DOI: 10.1016/s0973-6883(11)60157-6
|View full text |Cite
|
Sign up to set email alerts
|

20 Predictors for Need for Liver Transplants in Acute Zinc Phosphide Poisoning

Abstract: failure (ALF). In India, an unusual but not an uncommon cause of ALF is the ingestion of rodenticides containing zinc phosphide (Ratol ®). Overall survival following Ratol ® poisoning is poor without LT. Aim: The aim of this study was to identify clinical predictors to distinguish patients most likely to require LT following Ratol ® ingestion. Method: Retrospective data analysis of 30 patients admitted between January 2006 and April 2011 following Ratol ingestion was performed. Nine underwent living donor live… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Acute hepatic failure has also been reported which is often considered to be fatal and may warrant liver transplantation [8]. Severe prolonged hypoglycaemia has been reported following ZnP poisoning possibly due to impairment of glycogenolysis and gluconeogenesis [9].…”
Section: Discussionmentioning
confidence: 99%
“…Acute hepatic failure has also been reported which is often considered to be fatal and may warrant liver transplantation [8]. Severe prolonged hypoglycaemia has been reported following ZnP poisoning possibly due to impairment of glycogenolysis and gluconeogenesis [9].…”
Section: Discussionmentioning
confidence: 99%
“…A study from Kerala found MELD score of 31 on the sixth day or the presence of encephalopathy at any time after ingestion of zinc phosphide as a strong predictor of mortality without liver transplantation. 10 Liver transplantation is a potential therapy for patients who do not improve with supportive measures. However, the selection criteria for liver transplantation in ACLF needs to be better defined.…”
Section: Discussionmentioning
confidence: 99%